2010
DOI: 10.1242/jcs.071472
|View full text |Cite
|
Sign up to set email alerts
|

The cargo-selective retromer complex is a recruiting hub for protein complexes that regulate endosomal tubule dynamics

Abstract: Research Article 3703 IntroductionEndosomal protein sorting has a vital role in a number of physiologically important processes including antigen presentation, macromolecular nutrient uptake, growth factor receptor signaling and downregulation, autophagy and lysosome biogenesis (for reviews, see Sadowski et al., 2009;Saksena and Emr, 2009;Sann et al., 2009;Seaman, 2008;Lee et al., 2008). Recent studies of inherited diseases have identified several examples of genes encoding proteins that function in endosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
345
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 233 publications
(369 citation statements)
references
References 60 publications
20
345
1
3
Order By: Relevance
“…17 WASHdependent actin polymerization promotes scission of transport intermediates of the different endosomal routes and affects recycling, 17 degradation, 18 and retrograde pathways. 19,20 Inactivating variants in the gene encoding the WASH subunit strumpellin has been recently shown to cause a form of RSS/3C syndrome. 2 Variant in another component of the WASH complex, SWIP, was shown to be causal to non-syndromic ID.…”
Section: Discussionmentioning
confidence: 99%
“…17 WASHdependent actin polymerization promotes scission of transport intermediates of the different endosomal routes and affects recycling, 17 degradation, 18 and retrograde pathways. 19,20 Inactivating variants in the gene encoding the WASH subunit strumpellin has been recently shown to cause a form of RSS/3C syndrome. 2 Variant in another component of the WASH complex, SWIP, was shown to be causal to non-syndromic ID.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have shown that the LFa motifs within the FAM21 tail directly interact with VPS35 (Gomez and Billadeau, 2009;Harbour et al, 2010;Jia et al, 2012) promoting endosomal accumulation and the regulation of endosome to plasma membrane as well as retrograde endosome to Golgi trafficking. Importantly, our results suggest that recruitment by the retromer is required for normal FAM21 nuclear accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FAM21-VPS35 interaction is necessary for recruitment of WASH complex to endosomal membranes (Gomez and Billadeau, 2009;Harbour et al, 2010;Harbour et al, 2012;Helfer et al, 2013). Notably, a rare autosomal-dominant VPS35 mutation (D620N) has recently been identified as a cause of Parkinson's disease owing to destabilized retromer-WASH complex association and impaired autophagy (McGough et al, 2014;Zavodszky et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another important difference between retromer in S. cerevisiae and mammals is that mammalian retromer associates with a number of accessory proteins including the WASH complex and a RAB GTPase activating protein (GAP), TBC1D5. 6 The difference between retromer in S. cerevisiae and higher eukaryotes is intriguing but also important for understanding the molecular mechanisms of retromer-mediated endosomal protein sorting.…”
Section: Evolutionary Variations Of Vps29 and Their Implications Formentioning
confidence: 99%